Znaczenie wybranej zwierzęcej symboliki w parenetycznej homiletyce Dhuody z Septymanii (ok. 803-843) - Chudzikowska-Wołoszyn, Małgorzata (Vox Patrum, 2024)
The main purpose of this article is to familiarize the reader with the stock of animal symbols used in parenetic reflections of the Carolingian intellectual Dhuoda of Septimania, the authoress of the mirror manual (Liber manualis), addressed to her teenage son Wilhelm. The presented analysis will focus on discussing the provenance of the symbolic signatures used in the work. An attempt will also be made to characterize their role in Dhuoda,s rhetoric and teaching. At this point, it will be important to expose the individual interpretation and reflections of the mother-authoress in relation to the animalistic symbols drawn in Wilhelm’s memory. Dhuoda’s interpretation will also be set in a broader theological and exegetical context. It should be emphasized that for the Duchess of Septimania – as for all her contemporaries – the key to interpreting the world and its details was found in the mystery of Christ. Sorrounding nature was treated like a book, which was written with mystical allegories of the Creator. A skillful reading of the symbols given to men could lead him to ultimate wisdom, help him understand the mystery of the invisible God and, finally, also the essence of humanity. The exemplification of the symbols used in the Liber manualis, made for the purpose of this article, will also allow conclusions to be drawn about the intellectual formation of the Carolingian authoress, her literary technique, degree of the orginality, and rhetorical competence.